Mitochondria-targeted NIR fluorescent probe for detection of hydrogen sulfide and its application in monitoring food freshness and bioimaging - Yiyan Huang; Zhengkuan Tan; Xiaoyu Zhang; Haichang Ding; Jing Zhang; Chunmei Jian; Yuling Zeng; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

Synthesis of oxime-modified hollow spherical metal-organic frameworks for efficient uranium extraction from seawater - Weifeng Hou; Zhijian Li; Kai Tuo; Yougan Wang; Sanmei Liu; Congbin Fan (Journal of Environmental Chemical Engineering, 2025)

A diarylethene-based probe with HSO3−-activated fluorescence to photochromism: Its imaging application in living cells and zebrafish - Yinjie Wu; Zhihong Gong; Xiaoqian Wu; Yiyan Huang; Leilei Sun; Haichang Ding; Yu-Ling Zeng; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2025)

A turn-off xanthene-based fluorescent probe for detection of cysteine and its practical application in bioimaging and food samples - Na Tang; Kangshuo Xu; Ruian Sun; Haichang Ding; Yuling Zeng; Yuan Ji; Congbin Fan; Gang Liu; Shouzhi Pu (Analytica Chimica Acta, 2024)

A near-infrared turn-on fluorescent probe for the detection of hydrogen sulfide in water samples and food spoilage - Wenjuan Cai; Tian Xin; Yayi Tu; Leilei Sun; Guanming Liao; Gang Liu; Congbin Fan (Analytica Chimica Acta, 2024)

Mitochondria-targeted fluorescent probe with long wavelength emission for detecting H2S and its application in foodstuff, water and living cells - Ling Xie; Renjie Wang; Congbin Fan; Yayi Tu; Gang Liu; Shouzhi Pu (Food Chemistry, 2023)

A facile construction of bifunctional core–shell–shell structured magnetic metal–organic frameworks for detection and removal of tetracycline - Jin Li; Ruihong Yao; Bowen Deng; Zhijian Li; Kai Tuo; Congbin Fan; Gang Liu; Shouzhi Pu (Chemical Engineering Journal, 2023)

Selective krypton uptake through trap confinement, formation of Kr2 dimer, and light response in a photochromic and radiation-resistant thorium-diarylethene-framework - Mengjia Yin; Qingyun Zhang; Tingting Fan; Congbin Fan; Shouzhi Pu; Rajamani Krishna; Feng Luo (Chemical Engineering Journal, 2023)

A New High Selective and Sensitive Fluorescent Probe for Al3+ based on Photochromic Salicylaldehyde Hydrazyl Diarylethene - Zidi Wang; Lijuan Shu; Xinyue Luo; Yayi Tu; Junfei Lv; Gang Liu; Congbin Fan; Shouzhi Pu (Journal of Fluorescence, 2022)

A Highly Selective Hg2+ Fluorescent Chemosensor Based On Photochromic Diarylethene With Quinoline Unit - Liangtao Mao; Xiumei Li; Haichang Ding; Congbin Fan; Gang Liu; Shouzhi Pu (Journal of Fluorescence, 2022)

A Novel Diarylethene-rhodamine Unit Based Chemosensor for Fluorimetric and Colorimetric Detection of Hg2+ - Xiumei Li; Xue Li; Heng Zhao; Huimin Kang; Congbin Fan; Gang Liu; Shouzhi Pu (Journal of Fluorescence, 2021)

Comparison between two statistical downscaling methods for summer daily rainfall in Chongqing, China - Lijun Fan; Zhongwei Yan; Deliang Chen; Congbin Fu (International Journal of Climatology, 2015)
Two circulation index‐based methods were applied to downscale summer daily rainfall at four meteorological stations in Chongqing, China. One is a regression method ( CIM ) and the other a hybrid circulation classification plus regression method ( CPM ). Both methods used the same three circulation indices and surface specific humidity as predictors. In the first method ( CIM ), the indices and humidity were used directly as predictors and only one model was developed at each station. In the second method ( CPM ), the indices were further used to define circulation patterns using the objective Lamb‐Jenkinson classification scheme, and one model was built using humidity as the sole predictor for each pattern. Logistic regression was used to define rainfall probability, and a gamma distribution was fit using observations to randomly generate daily rainfall amounts. The two downscaling methods were validated and compared. The results suggest that (1) both methods yield consistently reasonable results with respect to occurrence and amount of daily rainfall, although they perform poorly in reproducing interannual and interdecadal variability, (2) specific humidity should be used as a predictor. Both methods were forced by two future scenarios of a global climate model ( GCM ) to demonstrate the added value with two methods. The downscaled scenarios show a shift towards larger rainfall values, accompanied by more frequent dry days. This shift is mainly attributed to a change in specific humidity. Despite the similar performances of the two methods, CPM gives a higher frequency of dry days than CIM , whereas CIM produces stronger intensity of rainfall than CPM . This provides additional information about the uncertainty in the projections.

Statistical downscaling of summer temperature extremes in northern China - Lijun Fan; Deliang Chen; Congbin Fu; Zhongwei Yan (Advances in Atmospheric Sciences, 2013)

A comparison study of the climatological air-sea heat fluxes estimated by different computational schemes of bulk formula - Fu Congbin; Robert Pyle; Fan Huijun (Advances in Atmospheric Sciences, 1994)

Variability in latent heat flux over the tropical pacific in association with recent two ENSO events - Fu Congbin; Henry Diaz; Fan Huijun (Advances in Atmospheric Sciences, 1992)